2014
DOI: 10.2337/dc13-2759
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dulaglutide Monotherapy Versus Metformin in Type 2 Diabetes in a Randomized Controlled Trial (AWARD-3)

Abstract: OBJECTIVECompare the efficacy and safety of monotherapy with dulaglutide, a once-weekly GLP-1 receptor agonist, to metformin-treated patients with type 2 diabetes. The primary objective compared dulaglutide 1.5 mg and metformin on change from baseline glycosylated hemoglobin A 1c (HbA 1c ) at 26 weeks. RESEARCH DESIGN AND METHODSThis 52-week double-blind study randomized patients to subcutaneous dulaglutide 1.5 mg, dulaglutide 0.75 mg, or metformin. Patients (N = 807) had HbA 1c ‡6.5% ( ‡48 mmol/mol) and £9.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
355
2
31

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(435 citation statements)
references
References 33 publications
47
355
2
31
Order By: Relevance
“…The HbA1c reduction observed at 26 weeks in the present study in Japanese patients with type 2 diabetes is consistent with the upper range of reductions seen in the global AWARD studies for dulaglutide (0.75 or 1.5 mg) 11, 12, 13, 14. It has been previously reported that GLP‐1 receptor agonists exert greater HbA1c‐lowering effects in Asian compared with non‐Asian people, and it has been suggested that differences in BMI between the ethnicities may be a contributing factor in the observed differential effects 19.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The HbA1c reduction observed at 26 weeks in the present study in Japanese patients with type 2 diabetes is consistent with the upper range of reductions seen in the global AWARD studies for dulaglutide (0.75 or 1.5 mg) 11, 12, 13, 14. It has been previously reported that GLP‐1 receptor agonists exert greater HbA1c‐lowering effects in Asian compared with non‐Asian people, and it has been suggested that differences in BMI between the ethnicities may be a contributing factor in the observed differential effects 19.…”
Section: Discussionsupporting
confidence: 89%
“…The safety profile of dulaglutide in this study (Table 2) was similar to that seen in previous GLP‐1 receptor agonist studies 11, 12, 13, 14, 17, 18. The most‐frequently reported adverse event was nasopharyngitis, reported by 12–13% of patients in the active treatment groups.…”
Section: Discussionsupporting
confidence: 83%
“…The improvement in FBG was sustained through the longest study duration of 104 weeks in AWARD-5 [31]. In AWARD-3 study (monotherapy vs. metformin), treatment with dulaglutide also resulted in significant reductions in postprandial glucose (PPG) from baseline after 2 weeks and this reduction lasted through the study [28]. Consistent with the early reduction in FBG and PPG, dulaglutide was shown to reduce HbA1c in patients with T2D as early as 4 weeks [28,30,31,33] after the start of treatment, and the reduction was shown to be sustained through 104 weeks [31].…”
Section: Early and Sustained Glycemic Controlmentioning
confidence: 99%
“…The range of HbA1c reduction from baseline to the primary end point with dulaglutide 1.5 mg was −0.78% to −1.64% and −0.71% to −1.59% for dulaglutide 0.75 mg, and −0.39% to −1.41% for active comparators ( Figure 3 and Table 1) in the seven studies included in this report [26][27][28][29][30][31][32][33]. Across studies, dulaglutide 1.5 mg was superior, based on HbA1c change from baseline, to placebo in AWARD-1, AWARD-5, and AWARD-8 (Table 1; placebo data will not be discussed further in the context of this manuscript), and superior to the active comparators evaluated: metformin, sitagliptin, exenatide BID, and insulin glargine (the comparator in two separate studies), and noninferior to liraglutide at the primary end point.…”
Section: Early and Sustained Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation